(untitled) (Conference Zone, 2022)
Sports and exercise, in addition to concentration, support the commitment to maintain a habit and do work that involves constant movement over time. Thus, it facilitates the appearance of a disciplined attitude that can be extrapolated to other areas of life. Regular exercise affects body appearance, reduces weight and body fat, and tones the body. This in turn affects self-description and self-awareness, making you feel more attractive, energetic and agile, and increasing your self-esteem. In addition, the fact of maintaining constant order and discipline makes us look more consistent and determined and able to fight for our goals. Exercise is a recommended exercise in the fight against substance abuse because it prevents and dampens the urge to consume and produces endogenous endorphins that are less needed for consumption, moreover, it inconsistent answer with. In this sense, the effect is also associated with changes in circadian rhythms. Indeed, there are times when sport is harmful. Because it’s not about you - don’t do anything using force (at least you have to look for spiritual strength to physically “get up and go to the gym”) and if you don’t have a goal. selfdefeating. And there is no need to force children to attend classes. At least nothing terrible will happen, and if the child refuses to attend classes regularly, the question arises as to whether everything in his department is in order and properly selected. Professional and amateur at first glance, the sport looks the same and there are current athletes, whose performances are different, from which the winner is determined and the title and titles are paid. Each condition of the participants in the tournament people tends to win, delivering during the maximum board and complete completion of training